The International Labour Organization and Management Development in Argentina - Amdam, Rolv Petter (2024)
This article explores how the International Labour Organization (ILO) introduced management development programs in Argentina as a pilot project in developing countries in the late 1950s. By studying how the ILO worked together with actors at the national level, the article reveals how the ILO’s original idea to focus on top management development was reshaped through a dialogue with local actors within the context of tripartite cooperation between the government, business organizations, and unions. While the initiative was successful during the project period, it collapsed when Argentina’s government closed down the national productivity center with which the ILO was cooperating. While the tripartite principle was valuable for the first achievements, it was extremely vulnerable without the support of all partners.